Culture studies on early development of Lessonia trabeculata (Phaeophyceae, Laminariales): Seasonality and acclimation to light and temperature. Issue 2 (23rd April 2013) - Murúa, Pedro; Westermeier, Renato; Patiño, David J.; Müller, Dieter G.
Summary: Lessonia trabeculata is an important economic and ecological algal resource of Chile. Due to intense use in abalone and alginate industries, severe problems of over‐harvesting are emerging. We compared sporophyte‐initiation and ‐growth in two populations from northern and southern Chile (Bahía Inglesa and Maicolpué) under laboratory conditions. Irradiance and temperature were the most important factors affecting gametophyte development. Meiospores harvested in spring exhibited maximum reproductive and growth potential, while spores released during autumn were moribund, and died within a few days. In both study sites, we found evidence for acclimation: Meiospores collected in summer required higher levels of irradiance and temperature for maximum development than winter spores. Juvenile sporophytes from both localities responded similarly to temperature and/or irradiance. The best conditions for recruitment of sporophytes from both localities were 15°C and white fluorescent light of 40–70 μmol m −2  s −1 . Although due to its low growth potential L. trabeculata is not a good candidate for mariculture, our results provide the necessary knowledge for laboratory‐based seedling production, which is needed for restoration and repopulation projects in damaged areas.